Plasma polymeric immunoglobulin receptor exacerbates lung injury in Klebsiella pneumoniae-induced pneumosepsis - Wang, Shuaiwei; Fu, Hao; Li, Xiaoqing; Xu, Hongrui; Bai, Yu; Jiang, Wenjun; Cheng, Xiaozhe; Chen, Na; Zhang, Yijie; Li, Wei (Frontiers in Immunology, 2025)
BackgroundPolymeric immunoglobulin receptors (pIgR) may enhance mucosal immunity or worsen an infection through transcytosis of polymeric immunoglobulins or infectious pathogens. The function of plasma pIgR in infections remains unknown.MethodsThe association of plasma pIgR with the occurrence and prognosis of sepsis was investigated using human plasma. The role and underlying mechanisms of plasma pIgR were investigated in mouse models of sepsis and primary alveolar type 2 epithelial cells (AT2).ResultsQuantitative proteomic and ELISA analysis revealed a significant association between plasma pIgR and the prognosis of patients of pneumonia-induced sepsis. Intravenous administrations of recombinant pIgR (r_pIgR) increased the mortality in mouse models of Klebsiella pneumoniae (KP)-induced pneumosepsis (KPS) and polymicrobial sepsis. r_pIgR also increased the injury score, caspase-11 and GSDMD-NT in the lungs of KPS mice. pIgR-neutralizing antibody (pIgR_Ab) exhibited opposite effects on animal survival in both sepsis models and on the injury score, caspase-11 and GSDMD-NT. Notably, r_pIgR did not affect the survival of Caspase-11-deficient KPS mice. pIgR immunoreactivity was absent in alveoli in normal mice, but emerged exclusively in AT2 in KPS mice. r_pIgR significantly reduced the level of biomarkers for AT2, but not AT1, whereas pIgR_Ab increased the level of AT2 biomarkers. In primary mouse AT2, heat-inactivated KP induced a marked increase in GSDMD-NT only in the presence of both r_pIgR and IgM.ConclusionsThis study demonstrates that plasma pIgR is a potential prognostic marker for sepsis, and likely contributes to AT2 pyroptosis and sepsis lethality through interaction with IgM, indicating a broad pro-pathogenic role of plasma pIgR in infectious diseases.